Cyclodipeptides: From Their Green Synthesis to Anti-Age Activity - Veronica Mosetti; Beatrice Rosetti; Giovanni Pierri; Ottavia Bellotto; Simone Adorinni; Antonella Bandiera; Gianpiero Adami; Consiglia Tedesco; Matteo Crosera; Greta Camilla Magnano; Silvia Marchesan (Biomedicines, 2022)
Cyclodipeptides (CDPs) or diketopiperazines (DKPs) are often found in nature and in foodstuff and beverages and have attracted great interest for their bioactivities, biocompatibility, and biodegradability. In the laboratory, they can be prepared by green procedures, such as microwave-assisted cyclization of linear dipeptides in water, as performed in this study. In particular, five CDPs were prepared and characterized by a variety of methods, including NMR and ESI-MS spectroscopies and single-crystal X-ray diffraction (XRD), and their cytocompatibility and anti-aging activity was tested in vitro, as well as their ability to penetrate the different layers of the skin. Although their mechanism of action remains to be elucidated, this proof-of-concept study lays the basis for their future use in anti-age cosmetic applications.